2013
DOI: 10.1007/s00249-013-0903-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium fluctuations of mechanically stretched single red blood cells detected by optical tweezers

Abstract: We study the thermal and out-of-equilibrium mechanical dynamics of single, living human red blood cells (RBCs) by combining two-probe passive and active microrheology techniques. Both experiments were performed quasisimultaneously on the same cell using two identical polystyrene probes, biochemically attached to the cell membrane. We obtained compelling evidence of nonequilibrium fluctuations in the RBCs under physiological condition and without the influence of any external chemicals. The spectral distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Previously, the fast characteristic recovery time τ fast in the order of 0.1 s was evaluated from the viscoelastic shape recovery after a local deformation by micropipette aspiration 5 42 43 , the parachute-shaped deformation by multiple optical trapping 44 , and the entire shear deformation by Couette flow 45 . Recent shape fluctuation analyses suggested that the time window of dissociation-reassociation of a spectrin network is about 100 ms on a single node level 8 29 , whose ATP-dependent, non-equilibrium response could be evidenced by the violation of fluctuation-dissipation theorem 9 30 . However, although the timescale of fast recovery τ fast = 0.1–1 s apparently seems to agree, it is not valid to directly correlate the dissociation-reassociation of a single node and the global shape change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the fast characteristic recovery time τ fast in the order of 0.1 s was evaluated from the viscoelastic shape recovery after a local deformation by micropipette aspiration 5 42 43 , the parachute-shaped deformation by multiple optical trapping 44 , and the entire shear deformation by Couette flow 45 . Recent shape fluctuation analyses suggested that the time window of dissociation-reassociation of a spectrin network is about 100 ms on a single node level 8 29 , whose ATP-dependent, non-equilibrium response could be evidenced by the violation of fluctuation-dissipation theorem 9 30 . However, although the timescale of fast recovery τ fast = 0.1–1 s apparently seems to agree, it is not valid to directly correlate the dissociation-reassociation of a single node and the global shape change.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental strategy proposed in the present work enables to fill the gap between the fast ( τ fast = 0.1–1 s) and extremely slow ( τ ex-slow ~1000 s) shape recovery, unraveling a new time window reflecting the “global” cytoskeletal remodeling. An increasing number of studies suggested that the ATP-dependent deformation of a erythrocyte is originated from the cytoskeletal remodeling by using non-equilibrium contour fluctuation analysis 8 9 13 29 30 38 40 and shear deformation experiments 27 28 47 . Therefore, the significant delay of T c found for ATP-depleted erythrocytes can be attributed to the decrease in the connectivity between spectrin networks and the associated proteins, such as protein 4.1R 49 , band-3 50 51 , ankyrin 52 , actin 53 , and spectrin itself 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation